The manipulation of the advertising discourse: rhetoric and stylistic aspects - Mokshin, Sergey (2021)
The article presents communicative, stylistic and rhetoric facets of the advertising discourse. The purpose of the study is to give consideration to communicative (rhetoric and stylistic) means of the advertising discourse in the role of suggestive practices acting as the mind manipulation. The main objective of such means is to sell goods via mass communication. Communicative impact is based on primary human emotions: joy, sorrow, fear and anger. The central task of the article is to analyze these aspects and their impact on the human conscience in the information transmitting process. Currently, mass communication media makes full use of the mind manipulation to draw attention to the advertised objects. To study such manipulation, the diverse methods are applied: discourse analysis, semiotic encoding and decoding as well as text analysis. When using these methods, we concluded that modern advertising communication focuses not so much on products and brands, but on the advertising piece. Advertisement videos demonstrate comfort, safety, ease of use of the product, etc. Advertisers pay attention to communicator qualities and the communication situation itself, which presents advanced features of a product. Communicators are most often well-known personalities acting as opinion leaders, so their messages are based on the advertiser confidence effect. The media space can include "seasonal" ads. This type of communication is presented in the form of brand advertising messages on the eve of various holidays or events linking a product with them. Online platforms and applications commercials are getting the significant evolvement in the TV advertising discourse. Online advertising drags TV content consumers into digital communication. Eventually, it should be emphasized that advertisers exert influence on the discourse as well as develop the advertising communication and, consequently, affect the recipients’ emotions. Consumers, in turn, guided by emotions, make a choice in favor of a particular product.